1999
DOI: 10.1128/jvi.73.6.4931-4940.1999
|View full text |Cite
|
Sign up to set email alerts
|

Feline Leukemia Virus Long Terminal Repeat Activates Collagenase IV Gene Expression through AP-1

Abstract: Leukemia and lymphoma induced by feline leukemia viruses (FeLVs) are the commonest forms of illness in domestic cats. These viruses do not contain oncogenes, and the source of their pathogenic activity is not clearly understood. Mechanisms involving proto-oncogene activation subsequent to proviral integration and/or development of recombinant viruses with enhanced replication properties are thought to play an important role in their disease pathogenesis. In addition, the long terminal repeat (LTR) regions of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 79 publications
3
14
0
Order By: Relevance
“…The U3-LTR region sufficient for gene transactivational activity does not contain a readable protein-coding frame. A specific RNA transcript for this region has been consistently detected in cells expressing only the U3-LTR as well as cells infected with the full-length virus (Ghosh and Faller, 1999). We have also demonstrated that LTR from nonpathogenic endogenous FeLV, which cannot transactivate cellular genes, does not make LTR specific transcript (Ghosh, Roy-Burman, and Faller, 2000).…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…The U3-LTR region sufficient for gene transactivational activity does not contain a readable protein-coding frame. A specific RNA transcript for this region has been consistently detected in cells expressing only the U3-LTR as well as cells infected with the full-length virus (Ghosh and Faller, 1999). We have also demonstrated that LTR from nonpathogenic endogenous FeLV, which cannot transactivate cellular genes, does not make LTR specific transcript (Ghosh, Roy-Burman, and Faller, 2000).…”
Section: Introductionmentioning
confidence: 69%
“…This finding suggested that the LTR may have some role in the induction of preleukemic hyperplasia in addition to its activity as an enhancer element. Other studies demonstrated that transient or stable expression of the U3-LTR region of Mo-MuLV or feline leukemia virus (FeLV) in fibroblasts of murine or feline origin, as well as in human lymphoid cell lines, induces expression of specific cellular genes, such as collagenase IV, monocyte chemotactic protein 1 (MCP-1), c-jun and MHC class I Ghosh and Faller, 1999;Koka, van de Mark, and Faller, 1991;Wilson, Flyer, and Faller, 1987). Upregulation of these genes occur at the level of transcription and is independent of the physical location of the LTR or the responding cellular genes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Membranes were hybridized with appropriate 32 P-labelled probe using Express-Hyb hybridization solution (Clontech) according to the manufacturer's protocol. DNA templates used for probe preparation were either the 341 bp U3-LTR insert in the 61E-LTR plasmid for LTR probe [11], or a PCR-amplified product of the envelope region of FeLV 61E using specific primers (FeLV EnvA and FeLV EnvB, Table 1).…”
Section: Northern Blotmentioning
confidence: 99%
“…Analysis of the necessary FeLV U3-LTR sequence for gene transactivation revealed that this region does not have any valid protein-coding frame. It was demonstrated previously that leukemogenic viruses such as Mo-MuLV and FeLV generate LTRspecific RNA transcripts [11,17]. Other studies on non-oncogenic endogenous FeLV LTRs demonstrated that they neither make specific transcripts like their exogenous counterpart, nor do they transactivate cellular gene expression [18].…”
Section: Introductionmentioning
confidence: 99%